Evaluasi Website Perguruan Tinggi menggunakan Metode Usability Testing - Agus Setiawan; R. Arri Widyanto (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Utilization of information technology on this day has become an unavoidable need. Utilization of website as a promotion event of an institution or organisation still not optimal because not follow usability aspect/usability. The interface of the university website should be a reflection of the university itself. Evaluation of the interface of the university website should be done to find out how high the usability level of university website development. Using usability testing method is expected to be able to measure the usability level of the university website to maximise the promotion of Higher Education in cyberspace. Methods to measure using quantitative methods by spreading questionnaires to the respondents. Research indicators use usability indicators that include Learnability, Memorability, Efficiency, Errors, and Satisfaction. The questionnaire tested its validity and reliability before use. Questionnaires are distributed freely to internal and external residents of Higher Education. 95 Respondents filled out questionnaires that had been scattered. Assessment method using a Likert scale with four levels, namely: Strongly Agree; Agree; Disagree; Strongly Disagree. The results of this study concluded that the university website has a final value of 2.77 where this value is still in the excellent category. The lowest value of the five aspects of usability is in the Errors aspect of obtaining a value of 2.65.